Item Quality Analysis of Concept Understanding and Problem Solving in Environmental Change Materials Using ANATES - Hermaya, Intan; Helendra; Vauzia; Arsih, Fitri (Jurnal Ilmiah Pendidikan Profesi Guru, 2024)
Teachers need help to measure students' understanding and problem-solving abilities, so these abilities are not measured well. This research analyses the quality of understanding concepts and problem-solving from environmental change material using the ANATES tool. Quantitative descriptive methods were used in this research. The research tool consists of objective questions and essays tested on class XI high school students after being verified by experts. The data collection method uses a questionnaire. The data collection instrument uses a questionnaire sheet. Data analysis techniques use quantitative analysis. The findings of the analysis show that although several things need to be modified, most of the items have good validity. The reliability of the instrument is in the high and very high categories. Question difficulty index, which varies from easy to complex. The majority of questions fall into the outstanding category for differentiating power. Based on the results of this research, the questions are generally of high quality. They can assess students' conceptual knowledge and problem-solving abilities related to environmental change material.